Pengembangan strategi bersaing dalam meningkatkan mutu layanan klaim - Baharudin adam; Sri Wahyuni (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2019)
This study aims to determine alternative competitive strategies at PT. Asuransi Wahana Tata in its efforts to improve the quality of claims services. Analysis technique using SWOT, IE Matrix, and QSPM analysis. Assessment of internal and esternal factors with interview techniques. The result of the research shows that the alternative of reliable corporate strategy is WO (Weekness-Opportunity) strategy, and the main strategy is the centralization of claims service process. The suggestion of this research is the company to carefully observe and evaluate external and internal factors and apply appropriate strategies to improve the service quality of claims by overcoming the company's weaknesses on claims service while taking advantage of existing opportunities by applying the claims service centralization. For further researchers interested in researching similar or similar issues may develop this research by adding other analytical tools such as BCG matrix, SPACE matrix, and grand strategy. It can also conduct research using other quantitative approaches. Keywords: Competitive Strategy, Service Quality, SWOT, IE Matrix, QSPM.